Four Models Including Fish, Seafood, Red Meat and Enriched Foods to Achieve Australian Dietary Recommendations for n-3 LCPUFA for All Life-Stages - Fayet-Moore, Flavia (Nutrients, 2015)
Populations are not meeting recommended intakes of omega-3 long chain polyunsaturated fatty acids (n-3 LCPUFA). The aim was (i) to develop a database on n-3 LCPUFA enriched products; (ii) to undertake dietary modelling exercise using four dietary approaches to meet the recommendations and (iii) to determine the cost of the models. Six n-3 LCPUFA enriched foods were identified. Fish was categorised by n-3 LCPUFA content (mg/100 g categories as “excellent” “good” and “moderate”). The four models to meet recommended n-3 LCPUFA intakes were (i) fish only; (ii) moderate fish (with red meat and enriched foods); (iii) fish avoiders (red meat and enriched foods only); and (iv) lacto-ovo vegetarian diet (enriched foods only). Diets were modelled using the NUTTAB2010 database and n-3 LCPUFA were calculated and compared to the Suggested Dietary Targets (SDT). The cost of meeting these recommendations was calculated per 100 mg n-3 LCPUFA. The SDT were achieved for all life-stages with all four models. The weekly food intake in number of serves to meet the n-3 LCPUFA SDT for all life-stages for each dietary model were: (i) 2 “excellent” fish; (ii) 1 “excellent” and 1 “good” fish, and depending on life-stage, 3–4 lean red meat, 0–2 eggs and 3–26 enriched foods; (iii) 4 lean red meat, and 20–59 enriched foods; (iv) 37–66 enriched foods. Recommended intakes of n-3 LCPUFA were easily met by the consumption of fish, which was the cheapest source of n-3 LCPUFA. Other strategies may be required to achieve the recommendations including modifying the current food supply through feeding practices, novel plant sources and more enriched foods.